Plasma Epstein-Barr viral DNA complements TNM classification of nasopharyngeal carcinoma in the era of intensity-modulated radiotherapy - Zhang, Lu (Oncotarget, 2015)
BACKGROUND: The objective of this study is to verify the prognostic value of pretreatment plasma Epstein-Barr viral deoxyribonucleic acid (pEBV DNA) levels in nasopharyngeal carcinoma (NPC) patients to complement TNM classification based on the application of the intensity-modulated radiotherapy (IMRT) technique. METHODS: In total, 1467 patients staged at I–IVa–b (M0) and treated with IMRT were retrospectively analyzed at our cancer center from January 2007 to December 2010. Patient survival among different stages and EBV DNA levels were compared. RESULTS: Outcome analyses of different stages and EBV DNA levels revealed that patients in stages II–III with low EBV DNA levels had similar survival as that of patients in stages IVa–b with low EBV DNA (5-yr overall survival (OS), 94.7% vs. 92.9% (P = 0.141), progression failure-free survival (PFS), 87.2% vs. 89.0% (P = 0.685), distant metastasis failure-free survival (DMFS), 93.5% vs. 92.4% (P = 0.394) and locoregional failure-free survival (LRFS), 93.8% vs. 96.3% (P = 0.523)). Conversely, patients in stages II–III with high EBV DNA had better survival than patients in stages IVa–b with high EBV DNA (5-yr OS, 82.7% vs. 71.7% (P = 0.001), PFS, 70.7% vs. 66.2% (P = 0.047), DMFS, 79.6% vs. 74.8% (P = 0.066) and LRFS, 89.3% vs. 87.6% (P = 0.425)) but poorer survival than patients in stages IVa–b with low EBV DNA (5-yr OS, 82.7% vs. 92.9% (P = 0.025), PFS, 70.7% vs. 89.0, (P < 0.001), DMFS, 79.6% vs. 92.4%, (P = 0.001), LRFS, 89.3% vs. 96.3%, (P = 0.022)). CONCLUSION: pEBV DNA is a strong prognostic factor for patients with NPC when complemented with TNM staging in the era of IMRT application.